Macroeconomic conditions, corporate defaults, and economic recessions - Xing, Kai (2017)
In this thesis, I investigate effective predictors for corporate defaults and measurement of economic recessions. I use corporate default probabilities in US industrial firms from April 1980 to December 2014 and effective predictors extracted from 92 macroeconomic and financial variables and I propose a framework to determine whether there is a dynamic in effective predictors for US corporate defaults.